Gambaran Pola Asuh Orangtua pada Anak Preschool Selama Pandemi Covid-19 - khaidarismail99; Riri Novayelinda; Ganis Indriati (STIKes Payung Negeri Pekanbaru, 2022)
Abstract Introduction: Parenting is an interaction between parents and children in carrying out parenting activities. The COVID-19 pandemic poses problems for parents in caring for and educating their children so that it can lead to parenting changes. The purpose of this study was to determine the description of parenting patterns for preschool children during the COVID-19 pandemic. Methods: This study used a quantitative descriptive research design using univariate analysis. The sample in this study was 98 respondents, namely mothers who have preschool aged children (3-6 years) based on inclusion criteria using purposive sampling technique. The measuring instrument used is a parenting style questionnaire consisting of 32 statements that have been tested for validity and reliability. Results: The results showed that parents who applied democratic parenting were 64 respondents (65.3%), while 14 respondents (14.3%) applied permissive parenting and 20 respondents (20.4%) applied authoritarian parenting. Conclusion: From the results of this study, it can be concluded that the parenting applied by dominant parents leads to a democratic parenting pattern where parents still have standard behavior and remain responsive to all the needs of their children. Suggestion: It is expected that parents can apply good parenting according to the age and stage of child development.